Edukasi Cerdas Menabung: Membangun Kebiasaan Finansial Anak SDN 091424 di Sidamanik Nagori Bah Biak - Nabillah Irbah Anjani; Malika Callista Lubis; Nazla Khairina; Hotmatua Paralihan (Pusat Riset dan Inovasi Nasional, 2026)
The habit of saving is an important foundation in building character and financial independence from an early age. This article aims to describe and analyze the implementation of a smart savings education program for students of SDN 091424 in Sidamanik, Nagori Bah Biak. Through an interactive and contextual educational approach, this program is designed to instill simple financial management values and encourage consistent saving behavior among elementary school children. The methods used include counseling, savings simulations, and an introduction to basic financial concepts through engaging and easy-to-understand learning media. The results of the activity show an increase in students’ understanding of the importance of saving and the emergence of positive behavioral changes in managing daily pocket money. Early financial education has been proven to be able to shape a thrifty and responsible mindset, so that it can be a valuable provision in facing future economic challenges. This program is expected to become an educational model that can be replicated in other elementary schools in rural areas.